Identificacao e mapeamento de areas de desertificacao sob clima umido no Brasil - Garcia, G. J.; Souto, J. J. (My University, 1989)
Environmental management mistakes are now strongly affecting some areas such as the agricultural areas of the southwest of the State of Rio Grande do Sul. The sandy soils in this region are adequate for the beefcattle activity, but ignoring technical reports great incentive was given to the soybean culture. The result was a very fast degradation of the arable layer and several places are considered real small deserts. The objective of this work is the mapping of these areas as well instable areas and gathering all the technical measures which were suggest for the land reclamation. -from English summary
Identification and mapping of areas under desertification in a humid climate in Brazil
Keywords: cattle; desertification; land degradation; land reclamation; Landsat; mapping; soil degradation; soybean; soybean culture; Brazil, Rio Grande do Sul